The Role of Parents in Learning Motivation in Grade 1 Students of SD Negeri 1 Dibal - Majidah, Muna; Novi Sila Alirga, Ananda; Muhammad Rifai, Dian (Melekliterasi Press, 2023)
Parents have a role in educating, motivating, facilitating and guiding children. The role of parents in providing motivation to children is very important and is highly expected when educating, however, there are challenges in providing motivation to learn which are influenced by several factors, making children's enthusiasm for learning low. This research aims to describe the role of parents in learning motivation in grade 1 students at SD Negeri 1 Dibal using qualitative methods with a phenomenological approach. The subjects of this research were the parents of 7 grade 1 students at SD Negeri 1 Dibal. Data collection techniques include observation, interviews and documentation. Based on the results of research that has been conducted, it shows that parents of students have played an active role in providing learning motivation to their children. The roles provided include providing learning facilities, giving rewards in the form of praise or goods, guiding, helping, monitoring and directing children in learning. However, there are obstacles in the availability of time and economic level. This condition influences children's willingness or motivation to learn less than optimally.